2007
DOI: 10.1038/ng2015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regions within 8q24 independently affect risk for prostate cancer

Abstract: After the recent discovery that common genetic variation in 8q24 influences inherited risk of prostate cancer, we genotyped 2,973 SNPs in up to 7,518 men with and without prostate cancer from five populations. We identified seven risk variants, five of them previously undescribed, spanning 430 kb and each independently predicting risk for prostate cancer (P = 7.9 × 10 −19 for the strongest Correspondence should be addressed to D.R. (reich@genetics.med.harvard.edu). COMPETING INTERESTS STATEMENTThe authors decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
573
10
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 611 publications
(622 citation statements)
references
References 15 publications
33
573
10
3
Order By: Relevance
“…Recent studies have identified multiple regions within 8q24 independently affecting the risk for prostate cancer. 18,19 In this study, we observed that GPAA1, at 8q24, is overexpressed in 41% of prostate cancer tissues. It will be interesting to explore whether the SNPs discovered in 8q24 18,19 affect regulation or transcription of GPAA1.…”
Section: Discussionmentioning
confidence: 60%
“…Recent studies have identified multiple regions within 8q24 independently affecting the risk for prostate cancer. 18,19 In this study, we observed that GPAA1, at 8q24, is overexpressed in 41% of prostate cancer tissues. It will be interesting to explore whether the SNPs discovered in 8q24 18,19 affect regulation or transcription of GPAA1.…”
Section: Discussionmentioning
confidence: 60%
“…This may have excluded a genuine second linkage signal, lying nearby, although it is doubtful that signals in such close proximity can be adequately resolved in most studies. However, it is possible that the wide clusters represent multiple co-located genes, as seen in prostate cancer (8q24) [113] and several other diseases. For the moment, we invoke Occam's razor in assuming that, generally, a single cluster represents a single underlying gene, with the linkage signal picked up over a substantial length of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the human MYC gene resides close to the 8q24 region that was found to be strongly associated with prostate cancer risk in recent genomewide association studies of prostate cancer. [25][26][27][28] Although no in vivo studies directly assessed the relationship between CRY2 and cancer, it is plausible that variations or mutations of CRY genes may alter cancer risk in a manner similar to that of PER2 because both are negative regulators of the circadian pathway. Since animal studies also suggest that circadian genes may be tumor suppressors, disruptions to human circadian genes might increase cancer risk by interfering with or inhibiting their tumor suppression activity.…”
Section: Discussionmentioning
confidence: 99%